Accuracy of blood pressure measurement across BMI categories using the OptiBP™ mobile application. (31st December 2022) - Caillat, Mary; Degott, Jean; Wuerzner, Arlene; Proençain, Martin; Bonnier, Guillaume; Knebel, Jean-François; Stoll, Chloé; Christen, Urvan; Durgnat, Virginie; Hofmann, Gregory; Burnier, Michel; Wuerzner, Grégoire; et al.
Abstract: Purpose: Obesity is a clear risk factor for hypertension. Blood pressure (BP) measurement in obese patients may be biased by cuff size and upper arm shape which may affect the accuracy of measurements. This study aimed to assess the accuracy of the OptiBP smartphone application for three different body mass index (BMI) categories (normal, overweight and obese). Materials and methods: Participants with a wide range of BP and BMI were recruited at Lausanne University Hospital's hypertension clinic in Switzerland. OptiBP estimated BP by recording an optical signal reflecting light from the participants' fingertips into a smartphone camera. Age, sex and BP distribution were collected to fulfil the AAMI/ESH/ISO universal standards. Both auscultatory BP references and OptiBP BP were measured and compared using the simultaneous opposite arms method, as described in the 81060-2:2018 ISO norm. Subgroup analyses were performed for each BMI category. Results: We analyzed 414 recordings from 95 patients: 34 were overweight and 15 were obese. The OptiBP application had a performance acceptance rate of 82%. The mean and standard deviation (SD) differences between the optical BP estimations and the auscultatory reference rates (criterion 1) were respected in all subgroups: SBP mean value was 2.08 (SD 7.58); 1.32 (6.44); −2.29 (5.62) respectively in obese, overweight and normal weight subgroup. For criterion 2, which investigates the precision errors on an individual level, the threshold for systolic BP in the obese group was slightly above the requirement for this criterion. Conclusion: This study demonstrated that the OptiBP application is easily applicable to overweight and obese participants. Differences between the reference measure and the OptiBP estimation were within ISO limits (criterion 1). In obese participants, the SD of mean error was outside criterion 2 limits. Whether auscultatory measurement, due to arm morphology or the OptiBP is associated with increasing bias in obese still needs to be studied. PLAIN LANGUAGE SUMMARY: What is the context? Hypertension and obesity have a major impact on population health and costs. Obesity is a chronic disease characterized by abnormal or excessive fat accumulation. Obesity, in combination with other diseases like hypertension, is a major risk factor for cardiovascular and total death. In Europe, the obesity rate is 21.5% for men and 24.5% for women. Hypertension, which continues to increase in the population, is a factor that can be modified when well managed. Blood pressure measurement by the usual method may be complicated in obese patients due to fat accumulation and the shape of the arm and can lead to measurement errors. In addition, the non-invasive blood pressure measurement can be constraining and uncomfortable. What is new? Smartphone apps are gradually appearing and allow the measurement of blood pressure without a pressure cuff using photoplethysmography. OptiBP is a smartphone application that provides an estimate of blood pressure that has been evaluated in the general population. The objective of this study is to assess whether OptiBP is equally effective in obese and overweight patients. What is the impact? The use of smartphones to estimate BP in overweight and obese patients may be a solution to the known bias associated with cuff measurement. The acquisition of more and more data with a larger number of patients will allow the continuous improvement of the application's algorithm.